2011
DOI: 10.1007/s12243-011-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of direct and cooperative transmissions in body area networks

Abstract: Body area networks (BAN) offer amazing perspectives to instrument and support humans in many aspects of their life. Among all possible applications, this paper focuses on body monitoring applications having a body equipped with a set of sensors transmitting in real time their measures to a common sink. In this context, at the application level, the network fits with a star topology, which is quite usual in the broad scope of wireless networks. Unfortunately, the structure of the network at the physical layer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Furthermore, asynchronous wakeup trigger mode is proposed for emergency traffic and to minimize the energy consumption. Ferrand, Maman, Goursaud, Gorce, and Ouvry (2011) use star topology to monitor different parameters of the human body in WBANs. Due to dynamicity of human body, the link between nodes and sink might be disconnected which results in loss of data.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, asynchronous wakeup trigger mode is proposed for emergency traffic and to minimize the energy consumption. Ferrand, Maman, Goursaud, Gorce, and Ouvry (2011) use star topology to monitor different parameters of the human body in WBANs. Due to dynamicity of human body, the link between nodes and sink might be disconnected which results in loss of data.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the same authors extended their study and found that the opportunistic relaying reduces significantly interference [5]. Importance in setting this topology has been also explored by considering whether the WBAN PHY is narrow-band [6] - [7] or UWB [8] and in all these studies significant performance benefits have been achieved. However, no works on the two-hop topology for intra WBAN communication, have so far taken into consideration transmissions flow optimization.…”
Section: Related Workmentioning
confidence: 99%
“…This fact motivated us to study the SE of relay-assisted cooperative transmission in UWB-based WBANs. For cooperative transmission, some related studies have been conducted in WBANs [10][11][12][13][14][15][16]. Particularly, channel modeling and system diversity were analyzed in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative scheduling schemes were proposed to decrease inter-BAN interference and increase packet reception rate of intra-BAN communications in [12]. In [13] and [14], packet error rate performance evaluation of two-hop links against the direct link was presented over narrow-band channels. In [15], the energy efficiency of cooperative transmission was considered from a relay selection perspective for UWB-based WBANs and the energy-efficient performance was analyzed with different relay regions.…”
Section: Introductionmentioning
confidence: 99%